Macrocryosectioning of the prostate: a simple technique. Issue 3 (1st March 2001) - Patriarca, C; Comi, A; Gazzano, G; Colombo, P; Campo, B; Coggi, G
Abstract : Whole mount sections of the prostate are widely used in many laboratories. Macrocryosections of the gland; that is, whole mount frozen sections of the prostate from radical prostatectomies represent a useful new research protocol. The technique is very simple and does not require expensive equipment.